Abertura, inserção e relacionamento da política criminal transnacional na sociedade em rede - Corrêa, Eduardo Pitrez de Aguiar (2015)
This study aims at contributing to a theory of internormative relationship in the scope of international sources that work on the standardization of criminal policy in States and of its legislative product, i. e., criminal law. Therefore, the investigation starts with the opening of the modern State and shows the change of the notion of Westphalian sovereignty which is needed for the construction of the form o f state that predominates in the beginning of the 21st century, the Cooperative Constitutional State. In this paradigm change, this study not only emphasizes the role of criminal law in the phenomenon of the internationalization of law but also suggests that criminal law – due to its relation with human rights – is responsible for determinant events in the process that change relations between national and international law broadly. In this context, it identifies a specific juridical domain, transnational criminal law, which is the product of a transnational criminal policy that leads to a global legal harmonization in certain areas of criminal law. Due to the new order imposed by the internationalization of law in general, and of criminal law in particular, this research also points out the need to highlight the different and permanent roles imposed on the relevant national and international actors when they face a multilevel normative structure which regulates in national law substantial domains protected by human and fundamental rights, changing the face and the role of international law. Based on the characteristics of this new legal structure, the study outlines a theoretical model of internormative relationship based on three categories: (i) networks, (ii) margin of appreciation and (iii) principle of the rule most favorable to the human being. They lead to a model of dialogic cooperation whose aim is to privilege the quality of the rule, rather than its hierarchy, in the decisions taken by judges and legislators, by using instruments of internormative connection.